Modelo de Resposta à Intervenção (RTI) para desenvolvimento das habilidades fonológicas com tutoria instrucional em contexto escolar: elaboração e controle de eficácia - Fukuda, Maryse Tomoko Matsuzawa [UNESP] (2016)
The use of response to intervention model (RTI), is a necessary model to assure that the difficulties of learning do not be the result of an instruction which does not prioritize the skills considered by the literature as predictors to the reading and writing learning in an alphabetic writing system, as the Brazilian Portuguese, this model, can assure to the teacher, by tutoring, the early identification of the real scholar risk to reading problems, avoiding then, the low scholar performance and minimizing the false-positive and false-negative result. The present research shows two studies: the Study I had by goal formulate an response to intervention Program with basis on phonological skills, associated to a grapheme-phoneme correspondence, and tutoring to the teacher, called PRIPROF-T, in collective way to scholars from 2nd grade of elementary education. Thus, there was a survey of intervention programs to be selected the necessary strategies. According to them, was achieved the selection of words, according to the established goal. The Study II had by goal verify the effectiveness of PRIPROF-T, elaborated in Study I, in scholar context, by tutoring mean and orientations to the teachers due to the development of skills related to reading and writing. From Study II, took part 117 scholars, from both genres, age groups from 6 to 7 years and 11 months age, regularly registered in 2nd grade of elementary education, besides the respective teachers. Got divided the scholars in two groups: Group I (GI): 60 scholars, distributed in three rooms of regular education, submitted to the PRIPROF-T; Group II (GII): 57 scholars, in other three rooms of regular education not submitted to the PRIPROF-T. In situation of pre and post- testing, subordinated all those to application of the Protocol of Early Identification of Reading Problems. The six teachers answered to a questionare in two moments: pre and post-testing. In the intervention step, occurred a guidance of the teachers from GI in relation to the application of activities from the Program of response to intervention elaborated. The GII remained with the regular scholar activities. In the statistic analysis of results, was used the Test of Signed Posts of Wilcoxon with the aim of verifying possible differences between both moments of observation (pre and post-testing), considered in evaluation of each group studied (GI and GII). The Test of Mann-Whitney, to verify possible differences between those groups. Other method was the Description of the categorized variables by Group and the analysis of Correlation of Spearman, to investigate the degree relation between the variables. The results have shown that the scholars from Group GI benefited from PRIPROF-T, denotating its effectiveness, because it favored the development of underlying skills to learning from reading and writing. The hypothesis of this research got proved, once the Program of response to intervention with basis on phonological skills, associated to a grapheme-phoneme correspondence, and tutoring to the teacher (PRIPROF-T) prepared, helped the teacher with identification of scholars with risk to reading problems and offered its prevention.